Volume 2: Coal, Biomass and Alternative Fuels; Combustion and Fuels; Oil and Gas Applications; Cycle Innovations 2001
DOI: 10.1115/2001-gt-0519
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Active Control of Combustion Instabilities on a Full-Scale Gas Turbine Combustor

Abstract: This paper presents the results of an investigation of active control of combustion instabilities in a natural gas, high-pressure, full-scale gas turbine combustor that was retrofitted with an Active Control System (ACS). The combustor test rig simulates the geometry, inlet airflow distribution, and pressurization of a can-type combustor that exhibits dynamic flame instabilities at some off-design operating conditions. Two essential features of the investigated ACS are 1) a real-time mode observer that identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Active instability control on a SiemensWestinghouse dry-low-NO x can-type combustor was reported by Johnson et al [407]. The combustion system consisted of eight main premixing passages dumping into a common flame zone.…”
Section: Can Combustormentioning
confidence: 98%
See 1 more Smart Citation
“…Active instability control on a SiemensWestinghouse dry-low-NO x can-type combustor was reported by Johnson et al [407]. The combustion system consisted of eight main premixing passages dumping into a common flame zone.…”
Section: Can Combustormentioning
confidence: 98%
“…Although numerous active instability control techniques have been developed and applied to laboratory-scale research combustors, only a few full-scale implementations have been reported on gas turbine combustors in the past [48,63,407], and more recently by Richards et al [408]. Practical full-scale implementations present several technological challenges.…”
Section: Implementation In Full-scale Gas Turbine Systemsmentioning
confidence: 99%
“…Some active control concepts involved speaker actuation [5][6][7][8][9][10][11] and others involved fuel modulation. [12][13][14][15][16] Fuel modulation is more applicable to aircraft gas turbine engines. Several techniques have shown some success in suppressing the frequency spectra of low frequency instabilities, with less success in suppressing the time domain pressure fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…Some active control concepts involved speaker actuation 4,5,6,7,8,9,10 and others involve fuel modulation. 11,12,13,14,15 Fuel modulation is more applicable to aero-type engines. But even the latter techniques have shown limited success in suppressing the frequency spectra of low frequency instabilities, and even less success in suppressing the time domain pressure fluctuations.…”
Section: Introductionmentioning
confidence: 99%